Risk Factors and Prognostic Analysis of Immune Checkpoint Inhibitor-Related Colitis in Lung Cancer - Wang S; Tian B; Wang H (Journal of Inflammation Research)
Shiyang Wang, Binhe Tian, Hanping Wang Division of Pulmonary and Critical Care Medicine, State Key Laboratory of Complex Severe and Rare Diseases, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, 100730, People’s Republic of ChinaCorrespondence: Hanping Wang, Division of Pulmonary and Critical Care Medicine, State Key Laboratory of Complex Severe and Rare Diseases, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, No. 1 Shuaifuyuan, Dongcheng District, Beijing, 100730, People’s Republic of China, Tel +86010-69158760, Email wanghanping78@163.comObjective: This study aimed to investigate the risk factors for immune checkpoint inhibitor (ICI)-related colitis and its impact on prognosis in the treatment of lung cancer.Methods: This retrospective, single-center, observational study included lung cancer patients who received ICIs treatment between January 2016 and January 2022. The correlation between immune-related colitis and prognosis was evaluated. Kaplan-Meier analysis was used to compare the median overall survival (OS).Results: Among the lung cancer patients treated with ICIs, the incidence of colitis was 5.88% (35/595). The severity of colitis was graded as follows: grade 1 (8 cases), grade 2 (15 cases), grade 3 (9 cases), and grade 4 (3 cases). Except for the 1 case that resulted in death due to grade 4 adverse events, the remaining patients showed significant improvement after corticosteroid intervention. Among the 35 patients with ICI-related colitis, complete remission was not achieved. Partial remission was observed in 11 cases, disease stability in 16 cases, disease progression in 7 cases, and death in 1 case. Among the included patients, 19 chose to continue ICI treatment after symptom relief. The overall survival for all participants was 34 months (IQR: 24– 36), while the overall survival for those who received ICI treatment again was 36 months (IQR: 32-NA), and for those who did not receive ICI treatment again was 32 months (IQR: 21– 35). Kaplan-Meier survival curve analysis showed that patients who received ICI treatment again had significantly better overall survival compared to other patients.Conclusion: Immune-related colitis remains a significant concern in lung cancer patients treated with ICIs and requires close monitoring and timely intervention. Restarting treatment after symptom relief can provide additional benefits for patients.Keywords: lung cancer, immune checkpoint inhibitors, colitis, risk factors, prognosis